Rare metal enrichment of the Tianbao trachytic complex, North Daba Mountains (South Qinling): Insights from textures and geochemistry of trachytes and Nb-REE minerals - Yan, Shuang; Niu, He-Cai; Zhao, Xu; Zhang, Qi-Bin; Zhang, Hai-Jun; Zhao, Xiao-Chen (Ore geology reviews, 2022)
[Display omitted] •Trachyte developed due to protracted magmatic differentiation of mafic magmas.•Rare metals initially enriched through magmatic differentiation.•Hydrothermal processes cause rare metal mineralization and precipitation. South Qinling hosts abundant alkaline igneous rocks characterized by rare metal mineralization, which, however, is not well understood, particularly for those extrusive alkaline magmatic systems. This study focuses on the Tianbao trachyte Nb(-REE) deposit located in the North Daba Mountains (South Qinling) and investigates textures and geochemistry of ore-bearing trachytes and Nb-REE minerals to reveal relative contributions of magmatic and hydrothermal processes to rare metal enrichment. Low K2O/Na2O ratios (0.26–1.64), depletions of Ba, Sr, and enrichments of Nb, Ta, Zr, Hf in the Tianbao trachytic complex resemble geochemical signatures of rifting-related alkaline igneous rocks, highlighting an intraplate rifting origin. Positive εNd(t) values (3.1 – 3.6) and constrained La/Yb (21.2 – 35.8) and Nb/Zr (3.7 – 4.8) ratios indicate that they might have originated from mixing of the asthenospheric mantle and metasomatized lithospheric mantle and formed due to protracted magmatic differentiation of coeval mafic magmas. Niobium and REEs in the Tianbao trachytic complex primarily originated from an enriched mantle source, and then upgraded to initial enrichment due to intense differentiation of the trachytic magmas. Niobium and REEs in the trachytic magmas were firstly incorporated into magmatic mineral phases (e.g., biotite, niobian titanite, niobian ilmenite and apatite) under relatively reduced (below the Ni-NiO oxygen fugacity buffer) conditions. With the differentiation of trachytic magmas, niobium, REEs and anion ligands (F-, CO32– and PO43-) got saturated in the late-stage alkaline melts and then entered the exsolved fluids. Ca-rich components should have been leached from the magmatic minerals during the hydrothermal stage and reacted with these ligands to develop Ca-rich hydrothermal mineral phases, including fluorite and calcite veins, allanite and apatite overgrowth under relatively oxidized (between the Ni-NiO and hematite-magnetite oxygen fugacity buffer) conditions. The remaining Nb and REEs finally precipitated as the economic minerals (e.g., allanite-(Ce), loparite-(Ce) and niobian Y-rich zircon) along fractures. Mass balance calculations indicate that these hydrothermal economic mineral phases account for the majority of Nb-REE reserve in the trachytic complex, and thus, the hydrothermal process might have played the key role in leading to Nb and REE concentrating to ore grade.